EFFECT OF ENSILING TIME ON THE QUALITY OF BANANA PEELINGS AND PEA Pon SILAGE - Niazi, A H K; Ali, Sakhawat; Kausar, Tasnim; Zafar, S I (Biological Sciences - PJSIR, 2021)
Si lage was prepared from banana peeli ngs (BP) as such (100%), BP + Lactobacillus , BP (with 70% moi sture), BP 70% , moisture + Lactobacillus, BP (50%) + pea pod (PP) 50%, BP (50%) + PP (50%) + Lactobacillus , PP (70% moisture) + Lactobacillus and PP with 70% moisture by mixing them and packed in pla stic bags at ambient temperature (28-35 °C) for 60 days of fennentation . Dry matter and protein contents showed gradual increase du ring the ensili ng period.